2017
DOI: 10.1371/journal.pone.0180413
|View full text |Cite
|
Sign up to set email alerts
|

LAG-3 potentiates the survival of Mycobacterium tuberculosis in host phagocytes by modulating mitochondrial signaling in an in-vitro granuloma model

Abstract: CD4+ T-cell mediated Th1 immune responses are critical for immunity to TB. The immunomodulatory protein, lymphocyte activation gene-3 (LAG-3) decreases Th1-type immune responses in T-cells. LAG-3 expression is significantly induced in the lungs of macaques with active TB and correlates with increased bacterial burden. Overproduction of LAG-3 can greatly diminish responses and could lead to uncontrolled Mtb replication. To assess the effect of LAG-3 on the progression of Mtb infection, we developed a co-culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Activated pDCs have a ~70-fold increase of LAG3 mRNA expression when compared with activated T cells (Workman et al, 2009), suggesting they could be primary mediators of an immunosuppressive environment (Graydon et al, 2019). We also showed that LAG3 expression is induced significantly in the lungs of macaques with PTB and correlates with increased bacterial burden, and LAG3 overproduction can diminish T cell responses (Phillips et al, 2017). Together, these results project pDCs as a key immune cell in the lungs of PTB macaques where they are primed for rapid ll Article type I IFN production, prolonged survival, and may contribute to suppression and exhaustion of T cell responses.…”
Section: Discussionmentioning
confidence: 51%
“…Activated pDCs have a ~70-fold increase of LAG3 mRNA expression when compared with activated T cells (Workman et al, 2009), suggesting they could be primary mediators of an immunosuppressive environment (Graydon et al, 2019). We also showed that LAG3 expression is induced significantly in the lungs of macaques with PTB and correlates with increased bacterial burden, and LAG3 overproduction can diminish T cell responses (Phillips et al, 2017). Together, these results project pDCs as a key immune cell in the lungs of PTB macaques where they are primed for rapid ll Article type I IFN production, prolonged survival, and may contribute to suppression and exhaustion of T cell responses.…”
Section: Discussionmentioning
confidence: 51%
“…Monocyte derived macrophages (MDMs) were generated from macaque blood and cocultured with CD4 + s, as described previously ( 73 ). A subset of MDMs was treated with IDO1-specific siRNA 24 h before M. tuberculosis -infection (multiplicity of infection = 10:1) ( Table S1 ) to inhibit IDO1 expression, as described previously ( 71 ).…”
Section: Methodsmentioning
confidence: 99%
“…LAG-3 favors M. tb survival by interfering with the mitochondrial apoptosis pathway. Thus, the silencing/down-regulation of LAG-3 in CD4 + T cell leads to an increase in M. tb killing, IFN-γ expression and decrease in mitochondrial electron transport (Phillips et al, 2017).…”
Section: Modulation Of Innate Immunitymentioning
confidence: 98%